MANAJEMEN PENDIDIKAN KARAKTER SEBAGAI PENINGKATAN KUALITAS PERILAKU RELIGIUS PESERTA DIDIK MTs. MUHAMMADIYAH 15 LAMONGAN: MANAJEMEN PENDIDIKAN KARAKTER SEBAGAI PENINGKATAN KUALITAS PERILAKU RELIGIUS PESERTA DIDIK MTs. MUHAMMADIYAH 15 LAMONGAN - AZ. Fanani; Anton Wahyudin (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2023)
Management of Character Education as Improving the Quality of Religious Behavior of MTs Students. Muhammadiyah 15 Lamongan, Thesis of the Islamic Education Study Program, Postgraduate Program, University of Muhammadiyah Surabaya. Supervisor I: Dr. M. Fazlurrahman Hadi, M.Pd.I., Advisor II: Dr. Mahsun Jayadi, M.Ag. This research is motivated by the fact that there are many young people today who prefer to behave in deviant ways as if they have forgotten their own identity. The problem formulation of this thesis is First, How is character education in MTs. Muhammadiyah 15 Lamongan, Second, How is the religious behavior of MTs Students. Muhammadiyah 15 Lamongan, Third, How is the management of character education in MTs. Muhammadiyah 15 Lamongan. The approach used in this research is qualitative descriptive. Data collection techniques using the method of observation, interviews and documentation. Data analysis consists of data reduction, data presentation and drawing conclusions. Checking the validity of the data is done through diligent observation, examination of teachers and Madrasah heads. The results of this study state that (1) character education in MTs Muhammadiyah 15 Lamongan has been implemented in a programmed, neat manner and has been carried out by all madrasa residents, (2) the religious behavior of students in general can be said to be very good, (3) The management of character education has been carried out quite well by Madrasahs from planning to evaluation.